Achieving superior hydrogen storage properties via in-situ formed nanostructures: A high-capacity Mg–Ni alloy with La microalloying. (1st February 2022) - Ding, Xin; Chen, Ruirun; Zhang, Jiaxin; Chen, Xiaoyu; Su, Yanqing; Guo, Jingjie
Abstract: Mg-based hydride is a promising hydrogen storage material, but its capacity is hindered by the kinetic properties. In this study, Mg–Mg2 Ni–LaH x nanocomposite is formed from the H-induced decomposition of Mg98 Ni1·67 La0.33 alloy. The hydrogen capacity of 7.19 wt % is reached at 325 °C under 3 MPa H2, attributed to the ultrahigh hydrogenation capacity in Stage I. The hydrogen capacity of 5.59 wt % is achieved at 175 °C under 1 MPa H2 . The apparent activation energies for hydrogen absorption and desorption are calculated as 57.99 and 107.26 kJ/mol, which are owing to the modified microstructure with LaH x and Mg2 Ni nanophases embedding in eutectic, and tubular nanostructure adjacent to eutectic. The LaH2.49 nanophase can catalyze H2 molecules to dissociate and H atoms to permeate due to its stronger affinity with H atoms. The interfaces of these nanophases provide preferential nucleation sites and alleviate the "blocking effect" together with tubular nanostructure by providing H atoms diffusion paths after the impingement of MgH2 colonies. Therefore, the superior hydrogenation properties are achieved because of the rapid absorption process of Stage I. The efficient synthesis of nano-catalysts and corresponding mechanisms for improving hydrogen storage properties have important reference to related researches. Graphical abstract: Image 1 Highlights: The hydrogenation activation energy of Mg–Mg2 Ni–LaH x composite is reduced to 57.99 kJ/mol. The enhanced hydrogenation capacities at 325 °C and 175 °C are 7.19 wt % and 5.59 wt %, respectively. In-situ formed LaH2.49 nanophase is proved to catalyze the hydrogenation process. High-density tubular nanostructure alleviates the "blocking effect" by facilitating H diffusion.